Perancangan aplikasi permainan labirin dengan tema suku indonesia berbasis android - Edwin Meinardi Trianto (Universitas Muhammadiyah Riau, 2023)
In another function as entertainment, game also has another function as a most effective learning media, therefore an education games become a most fun learning media for child. As problem mentioned, the author aware that educational games are the most popular learning media compared to theoretical learning in the school. Student less interested to learn Pancasila education, social science, and civic education or something like them, and there is no cultural diversity lesson in current curriculum which set by government like the previous year’s curriculum. Because that problem, intolerance and racism in Indonesia still high and massive in social media, became a sign that knowledge of Indonesian tribes too low. And about this case, author got inspiration to create and develop educational games the tittle “The Design of Introduction to Indonesian Tribes Game Application “GANTARA” based on Android”. This Educational Games develop by Unity 2D and Android-Based. By presenting features such as information and searching cultural attributes such as clothes, dances, food, weapons, musical instruments typical of the region with regional origins and quizzes with the theme of ethnic diversity in Indonesia. The method used to develop this app is Throw Away Prototyping, which shows several prototype options which selected by the Maria Fatima elementary school for grades 3-5 and teachers. Next implement test process using the black box test method and questionnaire, enhancing students interest in learning and creating educational games that help students learn and learn about Indonesian.